2020
DOI: 10.1002/csc2.20183
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of high‐yielding, short‐duration rice genotypes for tropical Asia

Abstract: Previous efforts to increase the yield of tropical rice (Oryza sativa L.) have focused on medium‐duration varieties. However, there is increasing demand for high‐yielding short‐duration varieties that can adapt to intensified cropping systems and climate change. Our goal was to identify physiological traits associated with high yield in elite short‐duration genotypes suitable for tropical Asia. We conducted field experiments in five consecutive growing seasons at the International Rice Research Institute, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…Similarly, chlorophyll and leaf area are crucial in determining the yield (Lu et al, 1994;Anyia, 2004;Kikuchi et al, 2017;Won et al, 2020), as higher densities of chlorophyll per unit leaf area have been observed in thicker leaves, enhancing the photosynthetic capabilities (Craufurd et al, 1999) of plants resulting in the vigorous and productive crop. Overall, our results suggested that the group 1 and 4 rice genotypes are associated with better photosynthetic efficiency and high iWUE, which can be selected for biomass improvement (Placido et al, 2013;Vikram et al, 2016).…”
Section: Leaf Gas Exchange and Physiological Traitsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, chlorophyll and leaf area are crucial in determining the yield (Lu et al, 1994;Anyia, 2004;Kikuchi et al, 2017;Won et al, 2020), as higher densities of chlorophyll per unit leaf area have been observed in thicker leaves, enhancing the photosynthetic capabilities (Craufurd et al, 1999) of plants resulting in the vigorous and productive crop. Overall, our results suggested that the group 1 and 4 rice genotypes are associated with better photosynthetic efficiency and high iWUE, which can be selected for biomass improvement (Placido et al, 2013;Vikram et al, 2016).…”
Section: Leaf Gas Exchange and Physiological Traitsmentioning
confidence: 99%
“…The 74 genotypes showed significant variability in days to heading (DH), which is a useful trait because early heading lines mature earlier (Won et al, 2020). Sixteen of the 74 genotypes flowered earlier than control entry Rex.…”
Section: Agro-morphological Phenotypementioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that for the rice crop, results showed that correlation between the beginning of flowering and grain yield depended on the climate conditions (Won et al, 2020). For most species, the beginning of flowering, though of high heritability, is highly affected by the environment, especially temperature and precipitation (Lizarazo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%